Analysis of low student learning motivation: implications for physical education learning in fourth grade - Marsudianto; Anung Priambodo; Setiyo Hartoto (STKIP Pasundan Press, 2026)
Low learning motivation in physical education limits active participation, perseverance, and the achievement of learning objectives. This study examines whether the small-sided games (SSG) approach can improve these conditions through a quantitative pretest–posttest control group experimental design. The population consisted of all fourth-grade students at Petemon State Elementary School in Surabaya (N=109), with a sample of 54 students selected through cluster random sampling (27 experimental; 27 control). Motivation was measured using a 5-point Likert scale questionnaire containing 25 statements that were proven to be valid (r=0.619) and reliable (r=0.801), so that changes in scores could be more reliably interpreted as changes in motivation rather than measurement error. The SSG treatment was given in 4 sessions, then the data were analyzed descriptively and inferentially (Shapiro–Wilk; paired sample t-test; α=0.05). The results showed that the experimental group increased from 78.59 to 85.29 and was significant (0.000), while the control group increased less from 76.62 to 79.44. This pattern reinforces that SSG is effective in increasing motivation, possibly because the activities are more interesting, enjoyable, and encourage active involvement, making it relevant as an adaptive and student-centered PJOK strategy.